HLA-A2-Restricted Epitopes Identified from MTA1 Could Elicit Antigen-Specific Cytotoxic T Lymphocyte Response - Wu, Yahong (J Immunol Res, 2018)
Overexpression of metastasis-associated protein 1 (MTA1) has been observed in many human malignancies and is significantly related to tumor invasion and metastasis, therapeutic resistance to radiation and chemotherapy, making MTA1 an ideal candidate tumor antigen. We identified several human leukocyte antigen- (HLA-) A2-restricted epitopes in MTA1 and evaluated their binding ability to HLA-A(∗)0201 molecules. Subsequently, a recombinant fragment encompassing the dominant epitopes, MTA1((1–283)), was expressed, and the abilities of the selected epitopes of MTA1 and the MTA1((1–283)) fragment to induce cytotoxic T lymphocytes (CTLs) were examined. Our results indicated that the epitopes and MTA1((1–283)) fragment elicited HLA-A2-restricted and antigen-specific CTL responses both in vitro and in vivo. The new epitopes identified here may help promote the development of new therapeutic vaccines for HLA-A2(+) patients expressing MTA1.